The Effects of Using Gamma Irradiated Wheat and Barley in Layer Diets on Egg Product Parameters and Quality - Turgay Yıldız; Necmettin Ceylan (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the effect of using gamma irradiated barley and wheat 0, 10 and 100 kiloGray (kGy) and enzyme supplementation on the egg product criterions and external and internal egg quality was examined. In this experiment, 36 weeks old, 324 Brown Nick laying hens were used for ten week. The study was a randomized complete block design with 9 dietary treatments within 6 blocks of 54 pens each 6 birds per pen. Although egg weight was not significantly affected by gamma irradiation; enzyme supplementation of barley based diet significantly increased egg weight compared to barley control group. As egg mass production was considered, enzyme and 100 kGy gamma irradiation significantly improved the egg mass production compared to barley control. The feed conversion ratio was significantly improved by using gamma irradiated barley and enzyme in barley based diets (P